Successful treatment of neonatal atrial flutter by synchronized cardioversion: case report and literature review - Monika Wójtowicz-Marzec; Barbara Wysokińska; Maria Respondek-Liberska (BMC, 2020)
Abstract Background Atrial flutter (AFL) is a supraventricular tachyarrhythmia. In the ECG tracing, it is marked by a fast, irregular atrial activity of 280-500 beats per minute. AFL is known to be a rare and also life-threatening rhythm disorder both at the fetus and neonatal period. AFL may result in circulatory failure, and in a more severe form, it may lead to a non-immune fetal hydrops. However, with early prenatal diagnosis and proper treatment, the majority of AFL cases show a good prognosis. Case presentation We report a case of a neonate who was born at 34 weeks of gestational age by C-section because of risk for birth asphyxia, based on abnormal CTG tracing, which had no characteristic rhythms for fetal decelerations. A third day his heart rate was 220/bpm. ECG has shown supraventricular tachycardia with narrow QRS. The administration of adenosine resulted in the obvious appearance of "sawtooth wave" typical for AFL. Arrhythmia was resistant to the therapy of amiodaron. Then cardioversion was performed and the rhythm converted to normal. Conclusions As neonatal AFL might be resistant to conventional pharmacotherapy, one needs to remember about the possibility of electrical cardioversion in the pediatric cardiology referral center. Moreover, CTG monitoring is of limited use because it does not record fetal heart rhythms > 200/min and echocardiography at the reference center is practically the only method to monitor the condition of the fetus with abnormal rapid heart rhythm.